Indebted and overweight: The link between weight and household debt - Susan L. Averett; Julie K. Smith (Institute for the Study of Labor (IZA), 2012)
There is a substantial correlation between household debt and bodyweight. Theory suggests that a causal relationship between debt and bodyweight could run in either direction or both could be caused by unobserved common factors. We use OLS and Propensity Score Matching to ascertain if household debt (measured by credit card indebtedness and having trouble paying bills) is a potential cause of obesity. We find a strong positive correlation between debt and weight for women but this seems driven largely by unobservables. In contrast, men with trouble paying their bills are thinner and this is robust to various specification checks.
Keywords: I10; I12; I14; 330; obesity; credit card debt; propensity score matching; Private Verschuldung; Körpergewicht; Schätzung; USA